Geo-resistivity data set for groundwater aquifer exploration in the basement complex terrain of Nigeria, West Africa - Raji, Wasiu Olanrewaju (Data Brief, 2020)
To delineate prolific groundwater aquifers in the basement complex terrain of Ilorin, Nigeria, West Africa, a carefully designed Electrical Resistivity Surveys were undertaken at eighty-five (85) stations using Vertical Electrical Sounding (VES) technique with Schlumberger array. Data acquisition system comprised SAS 3000 ABEM Resistivity Meter, a D. C. battery, four metallic electrodes, electrical cables, portable Geographic Positioning System (GPS), hammers, measuring tapes, and other accessories. In addition to the resistivity data, the geographic coordinates of the survey points were measured for ease of geo-referencing of the exact points where the data were collected and for secondary use of the data. The data acquired were processed, analysed and interpreted using auxiliary curve matching techniques and computer iteration method. The results were used to: evaluate the subsurface in terms of the different geo-electric layers, their thicknesses, depths, and resistivities; evaluate the groundwater potential of the aquifer; identify suitable sites for locating boreholes for groundwater exploitation; and recommend depths to borehole bottom in the different parts of the study area. The data presented can be reused to determine the protective capacity of the overburden material against groundwater contamination; to determine the engineering-geophysics and geotechnical properties of the rocks for Civil Engineering applications; for predicting groundwater flow models; and for mineral exploration within the area. The data presented can be used with other geophysical and geological data acquired from the same area for a better evaluation of the subsurface for multipurpose applications.